SCHOOLOGY IN THE EYES OF SAMPOERNA UNIVERSITY STUDENTS - Rayadi, Yansen; Wijanti, Widdy (PEOPLE: International Journal of Social Sciences, 2020)
The utilization of technology in postsecondary education is inevitable. The 21st-century education requires college students to actively collaborate with other learners yet engage with technology to create a more attractive and effective learning environment. Schoology is one of the platforms that enable users to create, manage, and share learning materials. Thus, this paper discusses the utilization of Schoology in Sampoerna University, which focuses on identifying (1) the way Schoology supports Sampoerna University students in achieving the learning goals, (2) the features of Learning Management System that bring positive impacts to the students, and (3) the viable improvements in the Schoology's features to boost student performance and stimulate collaboration. The study employs a quantitative method, which gathers the response from direct users to answer the research questions. Based on the results of the survey conducted to Sampoerna University students, Schoology is still a preferable online learning platform. However, Schoology developers should inevitably carry out continuous improvements to provide the optimum learning experience for Sampoerna University students.